CIHI Survey: Hospital Admissions via the Emergency Department: Implications for Planning and Patient Flow - Heather Dawson, Jaya Weerasooriya and Greg Webster (Healthcare Quarterly, 2008)
Over one million Canadians are admitted to hospitals each year via the emergency department (ED). These patients tend to be older, have more severe and multiple conditions or diseases and stay in hospital longer than patients admitted via other means. In 2005-2006, hospital admissions through EDs accounted for approximately 60% of acute care hospitalizations in Canada (excluding hospitalizations in Quebec and those among women admitted for childbirth and infants born in hospital). These patients accounted for 65% of in-patient days, 11% of which were alternate level of care (ALC) days. Given the importance of this patient population, Canadian Institute for Health Information (CIHI)'s recent study Understanding Emergency Department Wait Times: Access to Inpatient Beds and Patient Flow (CIHI 2007) explores the length of time patients spend in the ED while waiting for an in-patient bed and some of the characteristics of patients admitted via the ED in comparison with patients admitted via other means. This article highlights some of the findings of this report by providing an overview of patients admitted via the ED and their contribution to ALC days.